From Preservation to Advancement: Reconfiguring the Meaning of Culture in Indonesian Policy, 2017-2022 - Septiawan Ardiputra (Jurnal Ilmu Sosial dan Budaya Indonesia, 2023)
Indonesian cultural policy underwent a significant transformation following the enactment of Law No. 5 of 2017 on the Advancement of Culture. This study examines how cultural meaning was reconfigured in national policy between 2017 and 2022. Using qualitative document analysis, seven national policy documents were analyzed through deductive-inductive coding, within-document analysis, cross-document comparison, and thematic development. The findings reveal five major patterns: preservation is increasingly framed as adaptive; culture is institutionalized through data and planning; its functions expand toward development, welfare, and value creation; society is increasingly positioned as an active actor while the state assumes a facilitating role; and cultural policy increasingly addresses identity, inclusion, ecology, and international engagement. The study concludes that the Advancement of Culture does not replace preservation but reconfigures it as one function within a broader policy architecture that is more adaptive, development-oriented, institutionalized, and participatory.